Business and Operational Strategy for Service Based Port Company in Indonesia to Face Covid-19 Pandemic - Mohamad Toha; Adi Saptari; Supriyanto Supriyanto (President University, 2020)
Covid-19 pandemic has threatened the port support service industry in Indonesia. These threats are in the form of decreasing demand throughout the customer market, increasing competition in the industry, rising operating costs, and the emergence of operational issues on how to handle operational activities safely. To deal with these issues, XYZ one of port service company was selected. Primary and secondary data are then collected, SWOT are identified and analyzed and company’s business and operational strategies are then formulated. After formulating the business strategy using diamond strategy framework and developing operational strategi based on the business strategy requirement we conclude that the strategies to solve the company problems are strengthening its network, performing taper integration and strengthening operational excellence and customer intimacy simultaneously. The suitable operation strategy to support the above strategies are taper integration, maintaining external resources, integrated planning and control, implementation of tight integrated standard business process, and continuous improvement.